Genetic and immune factors underlying the efficacy of cetuximab and panitumumab in the treatment of patients with metastatic colorectal cancer - Krawczyk, Paweł Adam; Kowalski, Dariusz M. (Contemporary Oncology/Współczesna Onkologia, 2014)
Efficacy of monoclonal anti-EGFR antibodies (cetuximab, panitumumab) used in combination with chemotherapy or alone has been demonstrated in clinical trials of patients with mCRC. Both drugs block signaling EGFR pathway in malignant cells (blocking ligand binding and EGFR dimerization). Obtaining treatment responses with anti-EGFR agents is possible only in a selected subgroup of patients with mCRC. Successful treatment with cetuximab and panitumab is possible almost exclusively in patients without RAS mutations. Research on predictive value of EGFR gene copy number, PI3KCA gene mutations, P53 and PTEN, and EGFR their ligands concentrations is ongoing. Cetuximab, as IgG1 class antibody, can cause antibody dependent cellular cytotoxicity against neoplasm cells, while panitumumab, as IgG2 class antibody, does not induce such effect. Therefore a potential predictor cetuximab therapy may be the presence of different polymorphic forms of the genes for receptor immunoglobulin Fc fragments: FcRIIa and FcRIII subclasses.